Synthesis of High-Entropy Oxide Nanopowders with Different Crystal Structures by Electrical Explosion of Wires - Shuai Liu; Kangqi Liu; Liangwen Qi; Lanjun Yang (Nanomaterials)
High-entropy oxides are a new type of material that consists of five or more principal elements in an equimolar or nearly equimolar ratio. They have many excellent properties and are rapidly becoming a hotspot for the development of new high-performance materials. In this study, electrical explosion is used for the first time to synthesize high-entropy oxide nanopowders with different crystal structures. (FeCoNiCrCu)O is the rock salt structure, (FeCoNiCrTi)O is the spinel structure, and (CoNiTiCuZn)O contains the two phases. According to the TEM and EDS results, the distribution of the five metal elements in the electrical explosion products is comparatively homogeneous, and the particle size of the products is concentrated in 20–40 nm. Elements such as Ti are prone to the formation of spinel structure, and the element Cu is prone to the formation of rock salt structure. The study shows that the electrical explosion of wires is a new method for the synthesis of high-entropy oxide nanopowders.